Eksistensi Prodi Akidah Filsafat di Fakultas Ushuluddin dan Humaniora - Abdullah Karim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2014)
Philosophy of faith and Humanitiesdepartment is one ofthe important programs at the Faculty of Islamic Theology. In regardto the understanding and practicing of the true religion and avoid thedeviation and the emergence of deviant teachings, the sciences thatincluded at Philosophy of faith and Humanities department are thesciences which was very important to achieve the goal of study. Theexistence of Philosophy of faith and Humanities department isdepend on students quantity, the competent provider and integralpolicy of the Indonesian Ministry of Religious Affairs. For thatsome policies should be initiated for strengthening oftheologyfaculty existence.